If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 35 + 4(x + -3) = 7x + -12 Reorder the terms: 35 + 4(-3 + x) = 7x + -12 35 + (-3 * 4 + x * 4) = 7x + -12 35 + (-12 + 4x) = 7x + -12 Combine like terms: 35 + -12 = 23 23 + 4x = 7x + -12 Reorder the terms: 23 + 4x = -12 + 7x Solving 23 + 4x = -12 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 23 + 4x + -7x = -12 + 7x + -7x Combine like terms: 4x + -7x = -3x 23 + -3x = -12 + 7x + -7x Combine like terms: 7x + -7x = 0 23 + -3x = -12 + 0 23 + -3x = -12 Add '-23' to each side of the equation. 23 + -23 + -3x = -12 + -23 Combine like terms: 23 + -23 = 0 0 + -3x = -12 + -23 -3x = -12 + -23 Combine like terms: -12 + -23 = -35 -3x = -35 Divide each side by '-3'. x = 11.66666667 Simplifying x = 11.66666667
| (2a/5b)(3b/8) | | 31=4-9v | | (3y/y+3)+(9/y)+3=(27/y^2+3y) | | 2(v+2)=2v+20 | | -16x^2+350x+40=500 | | 5x+8=7x-8 | | 3(n+1)=n+19 | | 3(x)+4(y)=75000 | | X=2/5y | | 43x-4=77 | | 0.05x-1.82=0.708x-0.504 | | 1/3(6y-9)=13-2y | | 5(x+9)=2x+15 | | a/(-4)+14=20 | | 4(2y+1)-5=-10(y-5) | | 10(z+1)-3(z-3)=3(z-3)+3(z-3) | | 9x/8-x=x/40-2/5 | | 2x+6=4x+5-1 | | 24k+132=24k+144 | | 2x/3*21/2x | | 4x^20=10x+3x^4 | | 72-8c=32+8c | | x^3-7x^2-185x+975=0 | | 10m+4m^2= | | n/7+19=11 | | p-5-13p=150-10 | | 3/x-1(5x-5) | | -3x^2=25 | | 5x+1=8-(3x+2) | | 3(-2)(4)+(4/-2)^2 | | 0=-8x^2+68x | | 6=1-25 |